Immunomodulators secreted from parasitic helminths act on pattern recognition receptors - Tsubokawa, Daigo (Frontiers in Parasitology, 2023)
Excretory-secretory (ES) products from parasitic helminths contain immunomodulatory molecules, which regulate the host immune responses due to their successful tissue migration, maturation, and reproduction. A fraction of the immunomodulatory molecules target pattern recognition receptors (PRRs), such as the toll-like receptor, C-type lectin receptor, receptor for advanced glycation end products, and nucleotide-binding oligomerization domain-like receptor, which trigger activation of their signaling cascades, inducing innate inflammatory responses and adaptive immunity in hosts. This article reviews ES immunomodulators that act on PRRs identified in parasitic helminths, and their immune-regulatory mechanisms facilitated by PRRs. In addition, we describe the therapeutic potential of the ES immunomodulators for allergic and inflammatory diseases.